Respuesta :
Answer:
x=(-3+-sqrt15)/2
Step-by-step explanation:
Without using calculatorsoup,
we can use the quadratic formula for x^2+3x-3=0
using it we find:
x=(-b+-sqrtb^2-4ac)/2a
x=(-3+-sqrt3-4*1*-3)/2
x=(-3+-sqrt15)/2
For this case we must resolve the following expression:
[tex]x ^ 2 + 3x-3 = 0[/tex]
The roots will be given by:
[tex]x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2 (a)}[/tex]
We have to:
[tex]a = 1\\\b = 3\\c = -3[/tex]
So:
[tex]x = \frac {-3 \pm \sqrt {3 ^ 2-4 (1) (- 3)}} {2 (1)}\\x = \frac {-3 \pm \sqrt {9 + 12}} {2}\\x = \frac {-3 \pm \sqrt {21}} {2}[/tex]
We have two roots:
[tex]x_ {1} = \frac {-3+ \sqrt {21}} {2} = 0.7913\\x_ {2} = \frac {-3- \sqrt {21}} {2} = - 3.7913[/tex]
Answer:
[tex]x_ {1} = \frac {-3+ \sqrt {21}} {2} = 0.7913\\x_ {2} = \frac {-3- \sqrt {21}} {2} = - 3.7913[/tex]